Portfolios : assessment resource kit - Forster, Margaret. (Australian Council for Educational Research, 1996)
This contains: Different portfolios for different purposes; Working portfolios; Documentary portfolios; Show portfolios; Designing portfolio assessments; and a Summary of the portfolio design process.